Mafia sholawat: The shift of Sufism proselytization in Indonesia - Hasanah Fitri, Cinto; Riski Andria, Yoga; Romadi, Pipir (Journal of Islamic Management, 2026)
This research explains the shift of Sufism da'wah in Indonesia with the phenomenon of mafia sholawat in the current era. This research analyzes the shift in Sufism da'wah in Indonesia with the emergence of the mafia sholawat phenomenon, the factors that influence it, and its impact on Muslim society in Indonesia. The author uses a qualitative method with a netnography approach and literature review. By observing videos on social media and also articles related to the shift in Sufism da'wah and mafia sholawat. The results of this study show that the sholawat mafia packages Sufism da'wah with a different approach. This approach attracts young people and marginalized groups such as street children and punk communities to engage in religious activities. The findings reveal a polarized community response split into two groups. Some support it as an innovative da'wah strategy and a strategy that is easily accepted by the younger generation, while others criticize it as an activity that violates adab and can damage the image of Islam itself